The efficacy of some antifungals against the fungi causing onychomycosis in vitro among patients attending Tishreen University Hospital in lattakia - علي نورا; زينة حمامة; جمال خدام (Latakia University Journal -Medical Sciences Series, 2024)
Onychomycosis is one of the most common nail infections. Commonly, caused by dermatophytes, yeasts and molds. It is difficult to treat and has a long treatment period, accompanied by high recurrence rates. The clinical manifestations of this condition encompass alterations in nail color and thickness, and morphological anomalies that adversely impact on quality of life. Topical and oral medications are used to treat onychomycosis. Antifungal resistance can arise due to the frequent, haphazard and experimental administration of these medications in patients. The objective of this research was to evaluate the efficacy of various antifungals agents that are readily accessible locally in treating the fungi responsible for onychomycosis in individuals visiting the dermatology clinic at Tishreen University Hospital in vitro. Methods: The study included 62 patients with onychomycosis. It was diagnosed by direct microscopic examination and fungal culture. The fungal isolates were tested for susceptibility to fluconazole, terbinafine, and clotrimazole using the disk diffusion method. Results: We found that fluconazole was effective against most yeasts (83.3%), while terbinafine was less effective than fluconazole against isolated yeasts (2.4%). On the contrary, fluconazole exhibited a lower efficacy than terbinafine against dermatophytes (7%) (93%) consecutively, while clotrimazole was less effective than both fluconazole and terbinafine against isolated fungi.